Pseudopapillary Tumor of the Pancreas. An Algorithmic Approach - Igbinosa, Osamuyimen (JOP. Journal of the Pancreas, 2011)
Context Solid-cystic pseudopapillary tumor of the pancreas is a rare tumor, but has favorable prognosis even in the presence of distant metastases. It is often associated with diagnostic and therapeutic challenges. Case reports Described are two cases of solid-cystic pseudopapillary tumor of the pancreas managed in our hospital between January 2000 and January 2010. One female and one male with mean age of 42 years (range: 33 to 51 years). Data collected were: presenting symptoms, signs, imaging and management. Literature review was obtained from computer generated MEDLINE and Google Scholar search for solid-cystic pseudopapillary tumor of the pancreas between 1980 and 2010. Articles relevant to the scope of this paper were selected. The incidence of solid-cystic pseudopapillary tumors of the pancreas in our institution is 2 cases in 10 years; i.e., 0.2 cases/year. Clinical presentation include; palpable abdominal mass, vague abdominal discomfort, increasing abdominal girth, significant weight loss, nausea and vomiting in both patients. The mean diameter of the tumors was 7.0 cm (range: 5.9 to 8.0 cm). Pancreaticoduodenectomy was performed on both patients. None received adjuvant therapy and no cancer recurrence was detected on follow-up. Conclusion Solid-cystic pseudopapillary tumor of the pancreas is a rare tumor with a favorable prognosis even with distant metastases; therefore, attempts must be made to differentiate it from other pancreatic neoplasms. Clinical and radiological studies alone are insufficient to establish the diagnosis of a pancreatic mass and tissue biopsy should be sought. Surgery is generally curative and should be pursued independent of size and distant metastases. Image: Proposed algorithm for evaluation of suspected pancreatic lesion.